2015
DOI: 10.1007/978-3-319-16006-1_3
|View full text |Cite
|
Sign up to set email alerts
|

The Historical Time Frame (Past 1000 Years)

Abstract: This chapter summarises the climatic and environmental information that can be inferred from proxy archives of the Baltic Sea area during the past millennium (1000 years). The proxy archives mainly comprise tree-ring analyses together with historical documents on extreme weather events and weather-related disasters. In addition to the reconstructed climate, climatic conditions are simulated using a regional climate model covering the Baltic Sea area. The chapter focuses on three of the main climatic periods of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 98 publications
1
9
0
Order By: Relevance
“…Poland have been used only for air temperature reconstructions (e.g. Przybylak et al, 2005;Szychowska-Krąpiec, 2010;Niedźwiedź et al, 2015). In the present paper, this kind of proxy data is used for the first time to identified droughts occurring in the vegetation period.…”
Section: Discussionmentioning
confidence: 99%
“…Poland have been used only for air temperature reconstructions (e.g. Przybylak et al, 2005;Szychowska-Krąpiec, 2010;Niedźwiedź et al, 2015). In the present paper, this kind of proxy data is used for the first time to identified droughts occurring in the vegetation period.…”
Section: Discussionmentioning
confidence: 99%
“…13). Fires were also reported in Iława and Szczecinek (Nowosad and Oliński, 2019). Table 3 are shown.…”
Section: The Year 1540mentioning
confidence: 91%
“…This shift in the NAO index has been interpreted as the enhanced influence of easterly anomalies during the LIA. Moreover, the very strong cooling, long winters and droughts in the mid-15th century coincided with high pressure conditions of the Siberian High (Meeker and Mayewski, 2002; Klimenko and Solomina, 2010; Niedźwiedź et al, 2015) and transport of cold continental air to eastern Poland. In fact, according to Przybylak (2011) the 15th century in Poland was a time of the major continentalization of climate.…”
Section: Responses Of Selected Trees On Anthropressure and Climate Changesmentioning
confidence: 98%
“…The recorded decrease could have been associated with the aforementioned timber trade being a part of the economic activities of the Teutonic Order. On the other hand, climate factors should also be considered, as it was the time of the transition to the main stage of the LIA (Niedźwiedź et al, 2015). Wanner et al (2015) indicated that the LIA, especially the period between ca.…”
Section: Responses Of Selected Trees On Anthropressure and Climate Changesmentioning
confidence: 99%